(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
Language assessment is a fundamental component of English language teaching and learning. It provides valuable information about learners’ language abilities and supports educational decision-making. Effective assessment enables teachers to evaluate students’ progress, identify strengths and weaknesses, and improve instructional practices. In higher education institutions, particularly technical universities, language assessment plays a crucial role in ensuring that students develop the communicative competencies necessary for academic and professional success. This article examines the concept of language assessment and discusses major approaches to assessing listening, reading, and speaking skills. Drawing on the works of Alderson, Buck, Brunfaut, Hubley, and Isaacs, the paper explores key principles of language testing and highlights the importance of validity, reliability, and authenticity in assessment practices.